Acanthomatous ameloblastoma of anterior maxilla - Bansal M; Chaturvedi T; Bansal R; Kumar M (Wolters Kluwer Medknow Publications, 2010)
The unusual case of acanthomatous ameloblastoma occurring in maxillary left anterior region in a 13-year-old female child is presented with chief complaint of swelling in the upper left anterior region since one year and spacing between maxillary left central incisor and canine. Microscopic examination of surgically excised specimen revealed solid epithelial cell nests with peripheral palisading ameloblastic cells and the central squamous cell assemblage that was consistent with the findings of acanthomatous ameloblastoma type. Acanthomatous ameloblastoma is the extremely rare variant. The present report discusses issues related to the incidence of such formations in the target tissues.